Fermentation Effect of Cacao Beans Originate from Jember on Polyphenol-Flavonoid Content and Radical Scavenging Activity - Eva Agustriana; Herly Angga Valentino; Nanik Rahmani; Nuryati Nuryati; Hendy Firmanto; Rike Rachmayati; Siti Eka Yulianti; Isa Nuryana; Yopi Yopi; Puspita Lisdiyanti (ALCHEMY Jurnal Penelitian Kimia, 2023)
Cacao is attractive for its flavor and taste and its beneficial effects. Therefore, this commodity is promising to be developed as a functional food. Many studies reported the bioactive compounds in cacao beans and their health benefits. However, to attain desirable flavor and taste, the curing process of cacao beans is a common practice, in which fermentation is one of the processes. Despite its significance, fermentation also alters the bioactive components in cacao beans. To develop a functional food rich in bioactive compounds, measuring the bioactive contents of treated and untreated cacao beans is desired. For that reason, in this study, the analysis of total polyphenol, flavonoid, catechin, and epicatechin, as well as the radical scavenging activity of fermented cacao beans, was performed. The study revealed that fermentation negatively affected all parameters. Cacao beans fermentation up to 96 h resulted in the loss of 54% of total polyphenol, 77% of total flavonoid, and 56% of radical scavenging activity. Determination of the flavan-3-ol components, catechin, and epicatechin,  revealed that they were reduced as the fermentation occurred.